Knowledge Sharing Pada Mahasiswa Baru: Studi Kasus Pada Mahasiswa Baru Ilmu Perpustakaan Program Sarjana Universitas Indonesia - Rifni Raihana; Tamara Adriani Salim (Jurnal IPI (Ikatan Pustakawan Indonesia), 2020)
Knowledge sharing in University level happens at the core activites of University. Almost all academics in University are doing knowledge sharing. Knowledge sharing could be found at learning, teaching and community services process. College students and lecturers are the one who mostly doing knowledge sharing. In University, knowledge sharing become an important process because there are difference between learning and studying in High School and in Univeristy. This research used SECI Model to analyze knowedge sharing. SECI Model is used to analyzed the creation and transfer of knowledge developed by Takeuchi and Nonaka (1995). SECI is an acronym for Socialization, Externalization, Combination and Internalization. By doing knowledge sharing college students could get the exsisted knowledge and even new knowledge. The result of this research shows undergraduate students of library science at university of Indonesia batch 2019 are doing knowledge sharing and they are using LINE application as a media.